Investigation into the Mechanism of Action of Madhuca longifolia for its Anti-epileptic Activity - Patel, Sandip; Patel, Sandeep; Patel, Veena (Pharmacognosy Communications)
Background: Heart wood of Madhuca longifolia J.F. Macbr. (Sapotaceae) is used in traditional medicine of India to treat seizure. Objectives: The heart wood extract of Madhuca longifolia was investigated for anticonvulsant activity and the possible mechanism of action involved in this activity. Materials and methods: The anticonvulsant activity of the methanol extract of heart wood of Madhuca longifolia was assessed in pentylenetetrazole (PTZ) - induced convulsion in mice with benzodiazepine as standard drug. Mechanistic studies were conducted using both flumazenil, a GABAA-benzodiazepine receptor complex site antagonist, and naloxone a non-specific opioid receptor antagonist. Results: Madhuca longifolia at the dose of 400 mg/kg prolonged the onset time of seizure and decreased the duration of seizures compared to saline group (p < 0.001). Flumazenil and naloxone suppressed anticonvulsant effects of Madhuca longifolia. Discussion and conclusion: It appears that Madhuca longifolia may be useful for the treatment of absence seizures and that these effects may be related to its effect on GABAergic and opioid systems. This result suggests that Madhuca longifolia possesses biological active constituents which may contribute to the anti-convulsant activity of Madhuca longifolia. This supports the ethnomedical claims of the use of plant in the management of epilepsy.
Keywords: Pentylenetetrazole; Flumazenil; Naloxone